2011
DOI: 10.1097/dbp.0b013e31822bc7b7
|View full text |Cite
|
Sign up to set email alerts
|

Eating Patterns in a Population-Based Sample of Children Aged 5 to 7 Years: Association With Psychopathology and Parentally Perceived Impairment

Abstract: Eating behaviors in a general population cohort were differentially associated with impact and psychopathology. Picky eating was highlighted among other behaviors as having negative correlates. Better knowledge of how childhood eating behaviors impact on children and their association with psychopathology will aid adequate assessment and treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(76 citation statements)
references
References 27 publications
5
67
0
4
Order By: Relevance
“…Fussy eating has been reported in 7%-30% of preschoolers in the general population. [1][2][3][4] We previously identified 5.6% of children as fussy eaters using latent profile analysis. 5 This is in line with reports of other studies using a data-driven approach to define fussy eating.…”
Section: Discussionmentioning
confidence: 99%
“…Fussy eating has been reported in 7%-30% of preschoolers in the general population. [1][2][3][4] We previously identified 5.6% of children as fussy eaters using latent profile analysis. 5 This is in line with reports of other studies using a data-driven approach to define fussy eating.…”
Section: Discussionmentioning
confidence: 99%
“…The Childhood Eating Assessment Questionnaire is a 41-item parent-report questionnaire derived from the Child Eating Behaviour Questionnaire, the Childhood Eating Behaviour Inventory, and questions from the Standford Feeding Questionnaire. Micali et al [19] identified five eating behavioral patterns differentially associated with impact and psychopathology at age 5e7 years: (1) overeating/good appetite; (2) picky eating; (3) slow/poor eating; (4) delayed eating; and (5) snacking. Data on eating behaviors at age 5e7 years were available on 825 (42.5%) of the participating children at age 11e12 years (N ¼ 1,939).…”
Section: Methodsmentioning
confidence: 98%
“…At age 5e7 years, eating behavioral patterns were assessed using the Childhood Eating Assessment Questionnaire [19]. The Childhood Eating Assessment Questionnaire is a 41-item parent-report questionnaire derived from the Child Eating Behaviour Questionnaire, the Childhood Eating Behaviour Inventory, and questions from the Standford Feeding Questionnaire.…”
Section: Methodsmentioning
confidence: 99%
“…SE has been associated with impairment in emotional, physical, and social domains. [3][4][5][6][7][8] Both researchers and clinicians need to understand the level of severity at which SE causes impairment, so that practitioners can know when to intervene. 3 Parents can reliably identify SE, are concerned about the social and health implications of SE, and frequently seek professional help, especially from primary care providers.…”
Section: What This Study Addsmentioning
confidence: 99%